Indonesian banking performance based on BUKU - Juliana Kadang; Surayya Surayya; Muh. Fasial (Department of Management - Faculty of Business and Economics. Universitas Surabaya., 2021)
The improvement in the performance of Indonesian banking when the global economy is being hit by uncertainty is one of the best achievements. Acquiring profitability is accompanied by an increase in efficiency in using available resources to gain profit. This study aims to measure and analyze the performance of Indonesian banking based on Profit Efficiency. Profit Efficiency of a bank is analysed based on BUKU (Bank Umum Kelompok Usaha). The profit Efficiency is measured using the Sthocastic Frontier Analysis (SFA) Frontier 4.1 with the translog model of Alternative Profit Efficiency. The input variables used are: labor costs, physical capital costs and interest costs. The output variable used is the amount of credit and the amount of other productive assets. The model equation used is the Bank Activity Approach. The total sample was 19 commercial banks listed on the Indonesia Stock Exchange (IDX) and had financial reports from the year of 2010 to 2019. The results of banking Profit Efficiency measurement based on BUKU conclude that BUKU 2 indicated that each bank’s Profit Efficiency tends to be increasingly inefficient. BUKU 3 of profit efficiency of banks tends to be more efficient. BUKU 4 shows that banks in this group of Profit efficiency are increasingly efficient. This means that the greater the bank’s core capital, the more efficient it is in generating profits.